Pralidoxime and pesticide poisoning: A question of severity? - Walton, Emma Louise (Biomed J, 2016)
In this issue of the Biomedical Journal, we highlight new data supporting the use of pralidoxime in the treatment of cases of organophosphate poisoning, which also suggest that WHO treatment guidelines should be updated. We also learn about a modified surgical technique to repair severe spinal injuries, as well as new insight into the structure of human adenovirus that could inform vaccine development.